Trust the plan eaudiobook The rise of qanon and the conspiracy that unhinged america. - Sommer, Will (HarperAudio, 2023)
""A story so bizarre, only Will Sommer could report it." —Molly Jong-Fast The definitive book on QAnon from the reporter knows them best; Will Sommer explains what it is, how it has gained a mainstream following among Republican lawmakers and ordinary citizens, the threat it poses to democracy, and how we can reach those who have embraced the conspiracy and are disseminating its lies. The Storm is Coming. Trust the Plan. WWG1WGA. You've seen the letter Q on TV and in the news – it's been everywhere from Trump rallies to the January 6th insurrection. "QAnon" used to sound vaguely familiar, somewhat ominous, but not quite mainstream. But what was once a fringe conspiracy theory has now become a household name and its symbols recognizable around the world. How did this happen, who is actually involved, what do they believe, and what do they want? Daily Beast reporter Will Sommer has been on the ground with Q's followers since day one, and in Trust the Plan Sommer has written the definitive book on the movement—who started it and who grew it, what they really believe is going on, and what they want to see "the Storm" accomplish on the day of its reckoning. At once a character study and a journalistic exposé, Sommer lets his cast of characters do the talking as he visits them around the world, from their makeshift compounds to the rallies they are still holding. The great tragedy of this story is ultimately the legitimization of this ideology by mainstream politicians eager to gain access to a large and growing cohort of voters. Though 2020 brought the end of Trump's presidency, his following within the QAnon community has simply pivoted and grown stronger. Trust the Plan shows us in granular detail who we'll be up against for years to come, in the US and abroad. Understanding why and how something like Q happens is an indispensable exercise, and in showing us how we got here we can chart a path out. Supplemental enhancement PDF accompanies the audiobook.